The ninth month [large type] - Patterson, James, 1947-; DiLallo, Richard (Grand Central Publishing Large Print, 2022)
From the New York Times bestselling author of The Midwife Murders comes a twisted psychological thriller about a mother-to-be trying to find proof that she's being stalked, even when everyone around her distrusts her mother's intuition. Emily Atkinson leads a complicated life in New York City. She's a successful marketing executive who lives in a luxury apartment and enjoys a glamorous existence until she lands in the hospital with a double diagnosis: she parties too much--and she's pregnant. Her nurse and new best friend, Betsey, helps Emily rediscover how much she loves morning runs in the park and quiet nights at home. But as a series of women in her wealthy social circles go missing, Emily's pregnancy becomes decidedly high-risk.